MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA MELALUI PENERAPAN MODEL COOPERATIVE INTEGRATED READING COMPOSITTION (CIRC) PADA SISWA KELAS IV SD OPTIMUS PRIMEA SCHOOL TAHUN PELAJARAN 2022/2023 - Siahaan, Rachel Yoan; Sihombing, Maslan (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2023)
This research was motivated by the low reading comprehension ability of class IV students at Optimus Primea School. This research is a type of Classroom Action Research (CAR) which aims to improve students' reading comprehension skills through the application of the Cooperative Integrated Reading Composition (CIRC) model. This research was carried out in class IV of Optimus Primea School with a total of 21 students. This research consists of 2 cycles where each cycle consists of four stages, namely planning, action, observation and reflection. Data collection techniques are observation and tests. Data was analyzed using qualitative and quantitative analysis. The results of research on students' reading comprehension abilities in cycle I showed that 12 students (57%) had completed the KKM. After cycle I, students' reading comprehension ability increased again to 18 students who completed the KKM with a class completion percentage of 85%. Based on these findings, it can be concluded that the reading comprehension ability of class IV students at Optimus Primea School has increased after implementing the Cooperative Integrated Reading Composition (CIRC) model.